Problem Based Learning A Pathway to Critical Thinking and Digital Literacy in Geography - Rokhman, Ayla Yuli; Rusijono, Rusijono; Susarno, Lamijan Hadi (Jayapangus Press, 2025)
21st-century skills, such as critical thinking and digital literacy, have become essential in modern learning. This study aims to examine the impact of the Problem Based Learning (PBL) model on students' critical thinking and digital literacy skills in the topic of atmospheric dynamics at Sekolah Indonesia Kota Kinabalu, Sabah-Malaysia. The research design used a quasi-experimental approach with a nonequivalent control group design. The sample consisted of 34 students in the experimental group and 31 students in the control group. The experimental class implemented the Problem Based Learning (PBL) model, while the control class used conventional methods. The results showed a significant improvement in both variables in the experimental group, with N-Gain Scores categorized as effective. Problem Based Learning (PBL) helps students understand scientific concepts in-depth, identify real-world problems, and develop creative, technology-based solutions. These findings prove that Problem Based Learning (PBL) is an innovative teaching method that is effective in enhancing students' competencies, especially in preparing them to face global challenges and the digital era.